Про деякі теоретичні підходи щодо сутності діяльності персоналу органів та установ виконання покарань в Україні - Коваленко, В.; Колб, І.; Kovalenko, V.; Kolb, І. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті викладені результати наукових досліджень, що стосуються визначення змістовно сутнісних ознак, які складають поняття «персонал органів та установ виконання покарань», а також доведено їх взаємозв’язок та взаємодію з тими елементами, що витікають із соціально-правової природи професійної діяльності цих осіб.The article outlines the results of the scientific research concerning the definition of essential content features that determine the concept of «personnel of the bodies and institutions for the sentences execution» and their interrelation and interaction with those elements of the system which stem from the socio-legal nature of the professional activity of these individuals. The author supports the definition of «penitentiary institution staff» as the personnel of the institutions and bodies providing the sentences execution, which performs the role of a special stateauthorized subject of the system of execution of sentences and the activities carried out in the sphere of penitentiary profession and also represents a specialized pedagogical system, which continuously provides the personnel with professional qualified preparedness. As a subject, the personnel of the bodies and institutions for the sentences execution is simultaneously a system component of many other social systems, namely: a) the criminal-executive system (the system of institutions and penal bodies, which, in their turn, are legal entities for the enforcement of sentences); b) the system of criminal-executive activity as it is its direct medium and the physical entity of punishment execution; c) the professional qualification system of penitentiary activity, element of its professional penitentiary culture; d) specialized pedagogical system, which provides adequate professional qualification training of the personnel.
Some Theoretical Approaches to the Content Nature of the Personnel Activity in Penitentiary Bodies and Institutions in Ukraine
Keywords: кримінально-виконавча діяльність; сфера виконання покарань; органи та установи виконання покарань; суб’єкти кримінально-правових правовідносин; персонал; принципи; форма; зміст; criminal-executive activity; scope of punishment; penal bodies and institutions; subjects of criminal-legal relations; personnel; principles; form; content